Strategic Management for Rural Tourism Development inWanayasa, Puwakarta, West Java, Indonesia - Gunawijaya, Jajang; Gulfira Akbar, Poeti Nazura; Ansori, Sofyan (Journal of Indonesian Tourism and Policy Studies, 2016)
This paper reveals a strategic management case of rural tourism development based on tourism plan in Wanayasa, Purwakarta, Jawa Barat. Research was conducted in August 2015 with qualitative approaches i.e. interview and focus group discussion. In addition, some of data also produced from secondary sources such as government regulation and official website. Findings show that the only strength Wanayasa possessed is their ability in capturing projections of external factors, including identification of potential investors for their tourism. Apart from that quality, it is obvious that their rural tourism development is lack of clear vision & mission, indefinite internal analysis, and chaotic strategy formulation as a result of disorganized planning processes. With those conditions, it will be tough for them to formulate the true competitive advantage as a basic foundation of their tourism development. Besides, the community and local elites are now tend to expect more in investor funds instead of systematic strategic management by their own.